Frailty among older surgical patients and risk of hospital acquired adverse events: The South‐Western Sydney frailty and nurse sensitive indicators study. Issue 3 (24th February 2022) - McEvoy, Lynette; Richter, Matthew; Chen, Tanghua; Le, Ann; Wilson, Carol; Marov, Lynda; Gujraz, Poumansing; Gray, Leeanne; Mayahi‐Neysi, Mandana; Francis, Nevenka; Mai, Ha Thi; He, Steven; et al.
Abstract: Background: While advances in healthcare mean people are living longer, increasing frailty is a potential consequence of this. The relationship between frailty among older surgical patients and hospital acquired adverse events has not been extensively explored. We sought to describe the relationship between increasing frailty among older surgical patients and the risk of hospital acquired adverse events. Methods: We included consecutive surgical admissions among patients aged 70 years or more across the SWSLHD between January 2010 and December 2020. This study used routinely collected ICD‐10‐AM data, obtained from the government maintained Admitted Patient Data Collection. The relationships between cumulative frailty deficit items and risk of hospital acquired adverse events were assessed using Poisson regression modelling. This study followed the RECORD/STROBE guidelines. Results: During the study period, 44, 721 (57% women) older adults were admitted, and 41% (25, 306) were planned surgical admissions. The risk of all adverse events increased with increasing number of frailty deficit items, the highest deficit items group (4–12 deficit items) compared with the lowest deficit items group (0 or 1 deficit item): falls adjusted rate ratio (adj RR) = 15.3, (95% confidence interval (CI) 12.1, 19.42); pressure injury adj RR = 21.3 (95% CI 12.53, 36.16); delirium adj RR = 40.9 (95% CI 31.21, 53.55); pneumonia adj RR = 16.5 (95% CI 12.74, 21.27); thromboembolism adj RR = 17.3 (95% CI 4.4, 11.92); and hospital mortality adj RR = 6.2 (95% CI 5.18, 7.37). Conclusion: The increase in number of cumulative frailty deficit items among older surgical patients was associated with a higher risk of adverse hospital events. The link offers an opportunity to clinical nursing professionals in the surgical setting, to develop and implement targeted models of care and ensure the best outcomes for frail older adults and their families.